Application of Quantum Computing in the Design of New Materials for Batteries - Ahmet Demir; Emine Yildiz; Cemil Kaya (Journal of Tecnologia Quantica, 2024)
The background of this research focuses on the challenges of developing batteries with high capacity, efficiency, and long life. Quantum computing is considered a promising technology for designing new materials that can solve these problems. The purpose of the study is to examine the potential application of quantum computing in the design of battery materials that are more efficient and have better stability. The method used is a quantum simulation to model the interactions of atoms and molecules in various materials that have the potential to be used for batteries, such as lithium-sulfur, graphene, and sodium-ion. The results showed that lithium-sulfur-based materials have a high energy capacity but are less stable, while graphene is more stable with excellent conductivity despite a slightly lower energy capacity. These results provide new insights into the selection of battery materials based on the balance between energy capacity, conductivity, and thermal stability. The conclusion of this study confirms the importance of quantum computing in accelerating the development of more efficient and environmentally friendly battery materials, although further physical experiments are needed to verify the results of quantum simulations.